2023
DOI: 10.3390/dj11090214
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Artificial Intelligence-Driven Diagnostic Tools on Treatment Decision-Making in Early Childhood Caries: A Systematic Review of Accuracy and Clinical Outcomes

Abeer Al-Namankany

Abstract: Early detection and accurate prediction of the risk of early childhood caries (ECC) are essential for effective prevention and management. This systematic review aims to assess the performance and applicability of machine learning algorithms in ECC prediction and detection. A comprehensive search was conducted to identify studies utilizing machine learning algorithms to predict or detect ECC. The included (n = 6) studies demonstrated high accuracy, sensitivity, specificity, and area under the receiver operatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This can help provide faster and more reliable diagnosis and reduce human errors. 28 , 29 , 34 , 36 - 38 , 43 , 45 , 52 Besides that, AI has shown the capability to streamline the drug prescription process. 31 Moreover, one paper reported that AI can aid in patient triage by offering guidance and evaluating the severity and priority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…This can help provide faster and more reliable diagnosis and reduce human errors. 28 , 29 , 34 , 36 - 38 , 43 , 45 , 52 Besides that, AI has shown the capability to streamline the drug prescription process. 31 Moreover, one paper reported that AI can aid in patient triage by offering guidance and evaluating the severity and priority of cases.…”
Section: Discussionmentioning
confidence: 99%